Local management strategies and attitudes towards selected threatened or protected plant species in Limpopo Province, South Africa (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rasethe MT, Potgieter M, Pfab M. 2021. Local management strategies and attitudes towards selected threatened or protected plant species in Limpopo Province, South Africa. Biodiversitas 22: 3773-3784. Throughout South Africa, ordinary people are managing and using local natural resources in ways that enhance their lives, but there is a major concern about the sustainability of wild plant harvest. This study aims to investigate the current management strategies employed by local people in the Limpopo Province for selected threatened or protected plant species (TOPS). Semi-structured questionnaires were used to gather information from a total of 333 participants, i.e. 110 community members (CMs), 180 traditional health practitioners (THPs), and 28 traditional leaders (TLs), as well as from 15 conservation officers (COs). The study area included the districts of Capricorn, Sekhukhune, Mopani, Vhembe, and Waterberg. Results indicated that in all districts of the province most CMs and THPs reported that no one managed plant resources in their surrounding communal lands, though TLs indicated that the state was involved with management. Fifty-nine percent of THPs indicated that there are no traditional rules that are applied towards conservation of communal lands, yet 91% of other participants in the Mopani, Sekhukhune, and Capricorn districts indicated that traditional rules are followed. Most CMs in these three districts were allowed to participate in conservation initiatives, although most of them did not know that the plants they were using were threatened and protected in legislation. It is recommended that collaborative partnerships be initiated between government and TLs in relation to managing the threatened or protected plant species in communal lands.
Keywords: local conservation; management of plants; protected species; threatened species; TOPS-listed plants